1987
DOI: 10.1002/ana.410220515
|View full text |Cite
|
Sign up to set email alerts
|

Seizures during barbiturate withdrawal: Relation to blood level

Abstract: We studied 21 patients with complex partial seizures during phenobarbital (PB) or primidone withdrawal. Blood levels were measured daily, and seizure frequency was monitored by nursing staff and EEG-video telemetry. Patients were monitored for one week of baseline and for five weeks after PB tapering was initiated (withdrawal). Most were observed for at least one week after levels were undetectable. When ranked seizure counts were averaged, there was a tendency for seizure rates to be highest as PB levels pass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

1991
1991
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 23 publications
0
16
0
1
Order By: Relevance
“…Another study, however, failed to mention previous AEDs as playing a role in SE in 52 children (Yager et al, 1988). Theodore et al (1987) found no relationship between the rate of PB discontinuation and seizure frequency. In these studies it should be noted that the patients had been receiving AEDs for prolonged periods of time prior to drug discontinuation, while our patients had received AEDs for an average of only 15 days before abruptly stopping.…”
Section: Discussionmentioning
confidence: 95%
“…Another study, however, failed to mention previous AEDs as playing a role in SE in 52 children (Yager et al, 1988). Theodore et al (1987) found no relationship between the rate of PB discontinuation and seizure frequency. In these studies it should be noted that the patients had been receiving AEDs for prolonged periods of time prior to drug discontinuation, while our patients had received AEDs for an average of only 15 days before abruptly stopping.…”
Section: Discussionmentioning
confidence: 95%
“…The bioavailability of oral PB is more than 95% and the peak blood level of PB is 0.5–4 h. The t 1/2 of PB is 2–7 days [85]. Discontinuing PB should be done with caution because a case report showed an increase of seizure frequency in patients tapering the doses of PB while stabilized on another AED [86]. Twenty-five percent of PB is cleared by renal excretion in unchanged form [87].…”
Section: Introductionmentioning
confidence: 99%
“…A previous study reported an increase seizure frequency in patients tapered from PB or primidone, while stabilized on another anti-epileptic drug (AED) [4]. Our report is the first study in a patient who had been seizure-free for several years before the initiation of the PB taper and who once again became seizure-free after full PB discontinuation.…”
Section: Introductionmentioning
confidence: 67%